5-point airway (5-AIR) ultrasound protocol for confirmation of endotracheal intubation and position in paediatric patients undergoing surgery: A prospective observational study - Adhiraj Baruah; Zainab Ahmad; Vaishali Waindeskar; Shikha Jain; Roshan Chanchlani; Pranita Mandal; Amit Agarwal; Shristi Agarwal (Indian Journal of Anaesthesia)
Background and Aims: We devised and compared the accuracy and time required for a 5-point airway (5-AIR) ultrasound (USG) protocol for confirming endotracheal intubation (ETI) and endotracheal tube (ETT) positioning (ETP) with the current reference standard of quantitative waveform capnography (QWC) and auscultation. Methods: In this prospective observational study, 75 American Society of Anesthesiologists physical status I or II children between 2 and 12 years undergoing elective surgery were recruited. ETI and ETP were confirmed clinically and sonographically using the 5-AIR USG protocol, which involves real-time tracheal USG followed by bilateral pleural and diaphragmatic ultrasonography. Results: There was no oesophageal intubation in this study; hence, the accuracy of the USG protocol for ETI could not be determined. For ETP, 68 patients had correctly placed ETTs. The 5-AIR USG protocol identified 4 out of 7 endobronchial placements, resulting in a sensitivity of 100%, specificity of 57.14%, and an overall diagnostic accuracy of 96%. The mean time for confirmation of ETI by QWC (20.77 s (standard deviation (SD): 4.11 s; 95% confidence interval (CI): 19.84, 21.70) was longer than real-time tracheal USG (2.11 s (SD: 0.31 s; 95% CI: 2.04, 2.18) (P = 0.001). For ETP, the mean time for 5-point auscultation was 12.69 s (SD: 2.48 s; 95% CI: 12.19, 13.25) versus 6.39 s (SD: 0.54 s; 95% CI: 6.27, 6.51) for pleural USG (P = 0.001). Adding diaphragmatic scanning increased the mean time to 11.45 s (SD: 0.87 s; 95% CI: 11.25, 11.65) and 30.68 s (SD: 2.01 s; 95% CI: 30.22, 31.13) if a probe change was required (P = 0.001). Conclusion: The 5-AIR USG protocol was useful, fast, and demonstrated high diagnostic accuracy to confirm endotracheal intubation and position in paediatric patients. This protocol may be incorporated along with clinical signs, auscultation, and QWC to confirm endotracheal intubation and position.